Application of particle swarm optimisation in solving emission constrained economic dispatch - Razali N.M.M.; Teh Y.Y. (Institute of Physics Publishing, 2023)
Production of electricity has long been equated with emission of hazardous greenhouse gases and pollutants. One of the ways to reduce this negative impact is via emission constrained economic dispatch (ECED). The ECED is aimed to simultaneously minimize the total cost of generation and the total emission level. In order to overcome the limitations of the widely-used conventional method (CM) such as lack of flexibility and accuracy and the probability of achieving only local minima, meta-heuristic optimisers are gaining popularity. The paper presents the formulation of the ECED problem and proposes the use of Particle Swarm Optimizer (PSO) as a better alternative to the CM. The effectiveness of using PSO to solve the ECED problem as compared to CM is demonstrated and discussed. Published under licence by IOP Publishing Ltd.